2020
DOI: 10.1111/1744-9987.13468
|View full text |Cite
|
Sign up to set email alerts
|

Oral roxadustat three times weekly in ESA‐naïve and ESA‐converted patients with anemia of chronic kidney disease on hemodialysis: Results from two phase 3 studies

Abstract: Roxadustat is a hypoxia‐inducible factor prolyl hydroxylase inhibitor approved in China for anemia of dialysis‐dependent chronic kidney disease (CKD). Japanese hemodialysis patients with anemia of CKD previously naïve to, or converted from, erythropoiesis‐stimulating agents (ESAs) were enrolled in two open‐label, noncomparative studies of titrated oral roxadustat administered three times weekly. ESA‐naïve patients (n = 75) were randomized to roxadustat (initial dose, 50 or 70 mg) for 24 weeks; ESA‐converted pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 15 publications
5
61
1
1
Order By: Relevance
“…HIF stabilizers have been approved for the treatment of CKD-related anemia in China and Japan, including roxadustat, which has been approved in China to treat anemia in patients with DD-CKD and NDD-CKD 16,17 and in Japan for patients with DD-CKD. 18 We evaluated the efficacy and safety of roxadustat vs. placebo for the treatment of CKD-related anemia in patients with NDD-CKD.…”
Section: Introductionmentioning
confidence: 99%
“…HIF stabilizers have been approved for the treatment of CKD-related anemia in China and Japan, including roxadustat, which has been approved in China to treat anemia in patients with DD-CKD and NDD-CKD 16,17 and in Japan for patients with DD-CKD. 18 We evaluated the efficacy and safety of roxadustat vs. placebo for the treatment of CKD-related anemia in patients with NDD-CKD.…”
Section: Introductionmentioning
confidence: 99%
“…For all patients, a meal was provided approximately 3 h before administration of roxadustat, after which food and water were not allowed before dosing. After dosing, patients had to refrain from food and water intake for ≥ 2 h. A 100mg dose of roxadustat was selected because it allowed for potential increases in exposure without any safety concerns based on findings from previous studies [13][14][15]. In addition, this dose level was considered sufficient for the evaluation of the concentrations of roxadustat and its metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with HIF‐PHI is also associated with decreased blood ferritin level and hepcidin level 24,25 . Iron deficiency is associated with thromboembolic events, and clinical trials of roxadustat in Japan have reported increased incidence of thromboembolic events 26 . As treatment with HIF‐PHIs may decrease serum iron levels due to increased availability of iron for erythropoiesis, one should pay attention to avoid treatment‐induced reduction in serum iron levels.…”
Section: Recommendations On the Use Of Hif‐phimentioning
confidence: 99%